The Effect of Social Commerce Constructs on Purchase Intention in Social Commerce in Bandung City - Saputra, Febrian Eko; Komaladewi, Rita; Mulyana, Asep (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
The purpose of this study was to determine the influence of the Social Commerce Construct on Purchase Intention with the Trust Variable as a Mediating Variable in Social Commerce in the city of Bandung. This study uses a causal research model, which is a research model to analyze the relationships between one variable and another, and this study uses quantitative data. The data collection in this study is based on two sources, primary data obtained from distributing online questionnaires to TikTok social media users and secondary data obtained from libraries, journals, and websites. The population in this study were all residents of Bandung City who would make product purchase transactions through the TikTok Shop social media, with the sampling technique being purposive sampling which produced 240 respondents. Data analysis used in this research is descriptive analysis and Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this study are that Social Commerce Construct has a significant effect on Trust, Trust has a significant effect on Purchase Intention, Social Commerce Construct has a significant effect on Purchase Intention, and there is an indirect effect of Social Commerce Construct on Purchase Intention through Trust.